Corpporate Social Responsibility, Capital Intensity, Kualitas Audit Dan Penghindaran Pajak: Kepemilikan Institusional Sebagai Variabel Moderasi - Lia Ristanti (Jurnal Literasi Akuntansi, 2022)
Purpose: This research aims to find out and analyze the effects of CSR, Capital Intensity and Audit Quality on Tax Avoidance moderated by Institutional Ownership.Method: The samples used in this study were manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020 as many as 42 companies obtained by purposive sampling method. This research technique uses multiple linear analysis and moderated regression analysis.Finding: The results of this study showed that CSR variables had a significant negative effect on Tax Avoidance, Capital Intensity had no effect on Tax Avoidance, and Audit Quality had a positive effect on Tax Avoidance. Institutional ownership cannot moderate the influence of CSR, Capital Intensity and audit quality on tax avoidance.Novelty: The novelty of the study, the researchers added variables of institutional ownership moderation and different time periods. Institutional ownership was chosen because it had a considerable influence in overseeing management performance to run the company's operations as well as to see how much influence institutional ownership moderated in the study.